Hepatic encephalomyelopathy: a complication following liver cirrhosis caused by Budd-Chiari syndrome and HBV - Cheng, Jun; Jiang, Shou-Wei; Zhou, Zhong-Song; Sun, Qiu-Lin (The Journal of Infection in Developing Countries, 2014)
Progressive encephalomyelopathy is a rare neurological complication of chronic liver disease, even manifesting progressive spastic paraparesis. Few reports detailing the clinical and diagnostic aspects of this uncommon cause of neurological deterioration in patients with hepatic insufficiency have been published. Early recognition of this disorder will become more important in the future as patients with liver disease survive longer due to medical advances, including liver transplantation. The case of a patient with hepatic encephalomyelopathy associated with Budd-Chiari syndrome and HBV-related cirrhosis is presented.